Determination of the relative humidity at the parts-per-million (ppm) level in gases by a nanoporous alumina thin-film on a surface acoustic wave (SAW) resonator. Issue 2 (4th March 2022) - Alam, Shamim; Khan, Shakeb A.; Mittal, Upendra; Islam, Tarikul
Abstract: Moisture measurement in parts per million (ppm) in electronic gases and in liquids for different industrial applications is challenging and a costly affair. There are numerous critical applications of ppm moisture measurement systems such as transformer oil, sulfur hexafluoride gas (SF6 ) in switchgear and protection, and the electronic industry for integrated circuit (IC) fabrication. Conventionally chilled mirror hygrometer and laser spectroscopy are used but some low-cost solutions using the thin-film capacitive sensors are also available in the market. This paper presents the fabrication of an inexpensive miniature moisture sensor using a commercial low-cost surface acoustic wave (SAW) resonator of 433.92 MHz frequency. To detect moisture, a hydrophilic metal oxide film is deposited on the interdigital electrodes (IDTs) of the SAW device. The film thickness is optimized to provide a sharp resonating peak under dry humidity conditions. Experiments were conducted to determine the frequency shift in the peak with the variation of moisture in nitrogen gas from 6 to 460 ppm using a vector network analyzer. The maximum sensitivity was 24 Hz/ppm with correlation coefficient of linearity equal to 0.99. An effort was also made to develop a prototype meter to measure moisture in ppm. Important features of the sensor are linear response, inexpensive fabrication, and appreciable sensitivity in the ppm range.